2021
DOI: 10.1177/1556984521991519
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Feasibility and Patency Analyses of a New Distal Coronary Connector: The ELANA Heart Bypass

Abstract: Objective This preclinical study determines the feasibility and 6-month patency rates of a new distal coronary connector, the Excimer Laser Assisted Nonocclusive Anastomosis (ELANA) Heart Bypass. Methods Twenty Dutch Landrace pigs received either a hand-sewn ( n = 8) or an ELANA ( n = 12) left internal thoracic artery to left anterior descending artery anastomosis, using off-pump coronary artery bypass grafting. Six-month patency rates were demonstrated by coronary angiography and histological evaluation. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Our recent study demonstrated preclinical feasibility of the ELANA Heart Bypass technique (V2 prototype) up to 6 months of follow-up; however, the anastomotic leakage rate after construction was unacceptable. 6 The current study supports technical perioperative feasibility of the new V3 prototype and a reduced rate of anastomotic leakage. More important, the anastomotic remodeling was evaluated with regard to the conventional hand-sewn anastomosis.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Our recent study demonstrated preclinical feasibility of the ELANA Heart Bypass technique (V2 prototype) up to 6 months of follow-up; however, the anastomotic leakage rate after construction was unacceptable. 6 The current study supports technical perioperative feasibility of the new V3 prototype and a reduced rate of anastomotic leakage. More important, the anastomotic remodeling was evaluated with regard to the conventional hand-sewn anastomosis.…”
Section: Discussionsupporting
confidence: 75%
“…Surgery, anastomotic construction, transit time flow measurements, and coronary angiography were performed according to our previously published protocol and article. 5 , 6 The ELANA Heart Bypass was constructed in compliance with its instructions for use, creating a 0-degree side-to-side anastomosis (i.e., functional end-to-side). The hand-sewn anastomoses were constructed 0-degree end-to-side.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations